Implementation of Continuous Integration and Continuous Deployment (CI/CD) to Speed up the Automation Process of Software Delivery In the Production Process Using Node.Js, Docker, and React.Js - Nurhayati, Nurhayati (Jurnal Info Sains : Informatika dan Sains, 2024)
With the increasing amount of software that has been developed by developers, this encourages experts in the software field to release products with quality and updates on a regular and scheduled basis. In the software development process, teamwork is crucial, where a developer must work together with his colleagues. Of the various software development processes that occur in the IT Cyber Community, challenges often occur at the code integration stage. This challenge arises when a lot of code from different developers has to be combined. Not only that, the time required is very fast to get new features. Continuous Integration/Continuous Delivery (CI/CD) can be a solution to overcome this problem. Through the implementation of CI/CD, the software integration and delivery process becomes more automated, allowing developers to integrate code more regularly and minimizing the risk of problems that may arise due to human error and also delays in deploying a new feature. The automation process in React.js and Node.js software development using Docker and Jankins was successfully carried out by implementing Continuous Integration/Continuous Deployment in testing, code that was integrated more regularly and software delivery was faster. In the process, the time required to deploy a software can be minimized, which previously took a long time, can now be shortened, which previously took 8 minutes 48 seconds, now only takes 2 minutes 56 seconds.